Meningkatkan Motivasi Belajar Peserta Didik Melalui Penerapan Permainan Modifikasi Bola Kasti dengan Bola Voli pada Pembelajaran PJOK di SMPN 13 Surabaya Kelas VII A - M. Makhrus; Andhega Wijaya; Agus Suparno (Journal of Creative Student Research, 2024)
The aim of this research is to determine the increase in students' learning motivation in learning PJOK through a modified game of baseball and volleyball. The method used in this research is the classroom action research method (PTK). The stages of this research were divided into two cycles. From the data obtained in cycle 1, the average student learning motivation was 43.9%, and the data obtained in cycle 2 was 74.72%, with this there was an increase in the average average of 30.82. Thus, there is a considerable increase in students' learning motivation. Obtaining this data is also evidence of the success of providing a modified game of baseball with volleyball to increase students' learning motivation in learning PJOK.